Pengaruh Akuntabilitas dan Kewajaran Komprehensif terhadap Kinerja Keuangan pada Belanja Daerah Kota Palangka Raya Periode Tahun 2021 sampai Tahun 2024 - Zahratun Nupus; Vivi Oktari (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of accountability and comprehensive fairness on the financial performance of regional expenditures in Palangka Raya City from 2021 to 2024. Financial performance in regional expenditures in Palangka Raya City is measured using the expenditure efficiency ratio, regional financial independence ratio, and percentage of expenditure realization. This research design uses quantitative methods. This study utilizes secondary data. The data source population used in this study was obtained from the annual report on the realization of the regional expenditure budget in Palangka Raya City for the period 2021 to 2024. The sampling technique in this study used purposive sampling. The data analysis method in this study used multiple linear regression and the Statistical Product and Service Solution (SPSS) 23 program. The results of this study indicate that accountability and comprehensive fairness are very important and have a positive effect on the financial performance of regional expenditures in Palangka Raya City. These results support the efforts of the Palangka Raya City regional government to significantly improve financial performance.